Sobre a caracterização temporal de frases complexas com orações adverbiais finais com para em Português Europeu - Purificação Silvano; Luís Filipe Cunha (Revista da Associação Portuguesa de Linguística, 2016)
The main goal of this paper is to discuss the temporal behaviour of European Portuguese factive purpose clauses introduced by para (‘to’) + non-inflected Infinitives. We will argue that a posteriority temporal relation, resulting from the interaction between the lexical properties of the connective and the Result Rhetorical Relation, is crucial to understand the temporal possibilities displayed in these sentences. However, we will demonstrate that other semantic factors, such as the aspectual profile of the eventualities and the Rhetorical Relations that may arise in these constructions, also play a decisive role in determining the final temporal ordering of the clauses.